Analisis Faktor yang Berpengaruh pada Kecenderungan Kecurangan Akuntansi (Fraud): Studi pada LPD Kecamatan Tabanan - Putu Dian Pradnyanitasari; Ni Made Intan Priliandani; I Ketut Puja Wirya Sanjaya (Politeknik Negeri Batam, 2021)
The purpose of this paper is to examine the influence of the suitability of compensation, internal control of cash and individual morality to the tendency of the accounting fraud (fraud). There were 36 respondents who were workers in LPD Tabanan Regency using purposive sampling and multiple linear regression analysis was used to answer the research hypothesis. The study found that all the factors tested had a negative effect on the tendency of accounting fraud (fraud).